Rate Regulation, Capital Structure, and the Sharing of Interest Rate Risk in the Electric Utility Industry: Discussion - Carleton, Willard T. (Journal of Finance, 1978)
Willard T. Carleton, Rate Regulation, Capital Structure, and the Sharing of Interest Rate Risk in the Electric Utility Industry: Discussion, The Journal of Finance, Vol. 33, No. 3, Papers and Proceedings of the Thirty-Sixth Annual Meeting American Finance Association, New York City December 28-30, 1977 (Jun., 1978), pp. 750-751